2001
DOI: 10.1152/ajplung.2001.281.2.l435
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 MAP kinase in diperoxovanadate-induced phospholipase D activation in endothelial cells

Abstract: We previously demonstrated that diperoxovanadate (DPV), a synthetic peroxovanadium compound and cell-permeable oxidant that acts as a protein tyrosine phosphatase inhibitor and insulinomimetic, increased phospholipase D (PLD) activation in endothelial cells (ECs). In this report, the regulation of DPV-induced PLD activation by mitogen-activated protein kinases (MAPKs) was investigated. DPV activated extracellular signal-regulated kinase, c-Jun NH2-terminal kinase (JNK), and p38 MAPK in a dose- and time-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…In endothelial cells, S1P is capable of activating p38 mitogenactivated protein kinase (MAPK) (19), and p38 MAPK regulates PLD (69). Furthermore, we have shown in Beas-2B cells that S1P-induced p38 MAPK phosphorylation is 1-butanolinsensitive, whereas ERK1/2 phosphorylation is attenuated with 1-butanol.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In endothelial cells, S1P is capable of activating p38 mitogenactivated protein kinase (MAPK) (19), and p38 MAPK regulates PLD (69). Furthermore, we have shown in Beas-2B cells that S1P-induced p38 MAPK phosphorylation is 1-butanolinsensitive, whereas ERK1/2 phosphorylation is attenuated with 1-butanol.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, we have shown in Beas-2B cells that S1P-induced p38 MAPK phosphorylation is 1-butanolinsensitive, whereas ERK1/2 phosphorylation is attenuated with 1-butanol. 2 These two MAPKs, particularly p38, have been shown to be involved in NFB activation (69) and IL-8 synthesis (49,52,70). It stands to reason that parallel and concomitant signaling events occur when S1P binds to its receptor(s).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cPLA 2 -specific inhibitor pyrrolidin-1 also decreased the phosphorylation of p38 MAPK. PLD activation by norepinephrine in VSMC is partially inhibited by either a MEK1 inhibitor (PD98059) (Muthalif et al, 2000;Parmentier et al, 2001b) or a p38 MAP kinase inhibitor (SB203580) (Min do et al, 2002), although SB203580 did not inhibit PLD activity in endothelial cells (Natarajan et al, 2001). However, Ang II-stimulated PLD activity has been reported to be independent of extracellular signal-regulated kinase 1/2 MAPK in VSMC derived from hypertensive rats (Wilkie et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although the current study has not characterized any of the Michael adducts formed in lung microvascular ECs, it has been demonstrated that HNE-protein adduct accumulation reflects cellular toxicity compromising tissue survival during heart ischemia, ischemia/reperfusion injury, or pulmonary diseases (18, 19, 38 -40). Exogenously added or endogenously generated in cells, 4-HNE modulates protein function; examples include Na-K-ATPase (57), glucose transporter (58), MAPKs (7)(8)(9)(10)(11)24), phospholipases (1,4,5,59,60), protein kinase C (6), IK␤ kinase (61), and gene expression of ␥-glutamylcysteine synthetase (62). Thus, 4-HNE generated during lipid peroxidation can serve as an extracellular and intracellular signaling molecule altering cellular responses to stress and toxicity.…”
Section: Fig 11 4-hne Induces Actin Fiber Rearrangement In Ecsmentioning
confidence: 99%